(untitled) (International Journal of Food and Nutritional Sciences, 2022)
Current changes in society and economy, through global competition and work culture have made employees find difficulty in balancing the two important areas of their life; work life and family life which continually keep them under pressure that directed to dissatisfaction of job, as a result of this would in turn into imbalance in their work and private life. Work-life balance is about people having a measure of control over when, where and how they work. It increases effectiveness as well as improves satisfaction, in both the professional as well as personal lives. The success of any institution based on the performance of its employees, which in turn based on various variables. So, the present study aims to examine the “impact of work life balance on job satisfaction amongst elementary school teachers. The present paper presents a summary of the literature on the value of work –life balance and job satisfaction. The key independent variables work-life balance; long hours of work, pressure/stress on work, intention to change a job, flexible working conditions/environments which serves as an indicator of work-life balance while dependent variable job-satisfaction includes salary level, interpersonal relationship, spend time with family, balance between work and life, staff loyalty as it levers. A survey of 350 school teachers via self-administrated questionnaire with the help of quota sampling technique is conducted with the response rate of 83%. Four sets of hypothesis are developed which relate directly to the research question. SPSS is used to perform reliability, descriptive, correlation and regression analysis. The findings suggest that in schools work-life balance has not much impact on teacher’s job-satisfaction. The reason of such results may be due to the uncertain circumstances, the huge rate of inflation and smaller numbers of job opportunities, lack of application of nationwide laws etc. The last section of the paper concludes along with Recommendation to scope for Future Research.